2000
DOI: 10.1207/s15327590ijhc1202_2
|View full text |Cite
|
Sign up to set email alerts
|

Performance Benefits of Simultaneous Over Sequential Menus as Task Complexity Increases

Abstract: To date, experimental comparisons of menu layouts have concentrated on variants of hierarchical structures of sequentially presented menus. Simultaneous menus-layouts that present multiple active menus on a screen at the same time-are an alternative arrangement that may be useful in many Web design situations. This article describes an experiment involving a between-subject comparison of simultaneous menus and their traditional sequential counterparts. A total of 20 experienced Web users used either simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Time has been used to test the cognitive load required both in reading [35] and in menu navigation tasks [36]. Link selection times were recorded in seconds for each page, starting when the link menu was shown and finishing when a link label was clicked.…”
Section: Reading and Link Selection Timesmentioning
confidence: 99%
“…Time has been used to test the cognitive load required both in reading [35] and in menu navigation tasks [36]. Link selection times were recorded in seconds for each page, starting when the link menu was shown and finishing when a link label was clicked.…”
Section: Reading and Link Selection Timesmentioning
confidence: 99%
“…The effect of information retrieval task characteristics on the navigation process has been studied and task complexity has been recognized as one of the important factors that affect the efficiency of information seeking strategies [15][16][17]. Task complexity can be conceptualized from different approaches and measured using different methods.…”
Section: Task Complexitymentioning
confidence: 99%
“…Figure 1 shows an example of regular breadcrumbs. Hochheiser et al (1999) investigated the performance benefits of simultaneous over sequential menus and found that sequential menus are better suited for in- An example of experimental breadcrumbs formation query where some kind of hierarchy exists (Hochheiser et al 1999). In another study by Zaphiris et al (1999), in-place expandable menus in web environment present a hierarchy of choice to users and reduce backtracking and lostness.…”
Section: Research Frameworkmentioning
confidence: 99%